Delighting in the Torah : the affective dimension of Psalm 1 - Martin, Lee Roy (Old Testament essays, 2010)
It is argued in this article that the common interpretation of Ps 1 as a call for obedience, a view exemplified by Walter Brueggemann's influential article, "Bounded by Obedience and Praise: The Psalms as Canon," does not quite capture the emphasis of the text. While it is true that Ps 1 affirms the lifestyle of the "righteous," righteousness is not limited to or equated with "obedience." The psalm points to the affections rather than to behaviour as the key element of the righteous person - "his delight is in the Torah of Yahweh" (Ps 1:2). Instead of calling for obedience to the Torah, Ps 1 evokes affection for the Torah. This important move suggests that the study of biblical poetry in general and of the Psalms in particular can benefit from an approach that is attuned to the passions that are inherent in the text and the passions that are brought to the text by the interpreter.